Biology aspects of Dictyla monotropidia (Hemiptera: Tingidae) in laurel trees Cordia alliodora (Boraginaceae) - MARTÍNEZ-C., HAROL ENRIQUE; OSPINA, CARLOS MARIO; MONTOYA, ESTHER CECILIA; CONSTANTINO, LUIS MIGUEL; BENAVIDES-MACHADO, PABLO (Revista Colombiana de Entomología, 2012)
The lace bug, Dictyla monotropidia, is the main insect-pest of laurel tree Cordia alliodora in Colombia. This insect feeds on leaves causing their dead and making them fall prematurely onto the ground. With the purpose of understanding some aspects of the biology of D. monotropidia, we studied its population dynamics and life cycle. We estimated the total number of insects on the trees and onto the soil, monthly during a year, in a 0.8 ha C. alliodora crop in Manizales. The life cycle of the insect was obtained from insects reared in a screen house at 22.4 ± 5.5 ºC and 66.8 ± 16.6% HR. We observed significant differences in the average percentage of infested leaves in the trees being higher in March 2009 (57.4%) and lower in January 2010 (1.6%). We found statistical differences in the number of insects in the trees along the year, with an average of 1.655 ± 361 individuals in April and 135 ± 64 in January. Individuals onto the ground ranged between 10.5 ± 2.4 and 245.5 ± 76.8 along the year. The average life cycle of D. monotropidia, from egg to adult was estimated in 44 ± 0.95 days, being 15.5 ± 0.1 for eggs, 28.5 ± 0.85 for the five nymph stages and a total duration of the adult of 115 ± 2.4 days. The control of this insect should be performed on the trees and on infested leaves on the ground.